PENGARUH MODEL STORYTELLING TERHADAP KETERAMPILAN BERCERITA BERBANTU MEDIA WAYANG NUSANTARA PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SD 2 KALIWUNGU - Rohmini, Siti Luvikasari; Dhina Cahya Rohim; Devy Aufia Abshor; Amalia Rahmawati; Deki Wibowo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of learning models storytelling using Indonesian wayang media for storytelling skills in class V of SD 2 Kaliwungu. This type of research is Quantitative with a Quasi-Experimental Pretest-Posttest Design, with research subjects of class V students at SD 2 Kaliwungu, totaling 40 students. The data collection techniques used in this research were tests, observation, interviews, and student response questionnaires. Based on the Normality test, results pretest-posttest the experimental class shows a significance value of 0.244 and the results pretest-posttest the control class shows a significance figure of 0.078, so it can be concluded that the data is normally distributed. Based on the Paired sample T-test analysis, it is known that the Sig (2-tailed) value is 0.001 due to the sig value. (2-tailed) is less than 0.05, so it can be concluded that the learning model storytelling Using Indonesian wayang media has an effect on the storytelling skills of class V students at SD 2 Kaliwungu.